2017
DOI: 10.1080/07370016.2017.1340556
|View full text |Cite
|
Sign up to set email alerts
|

US Healthcare Experiences of Hispanic Patients with Diabetes and Family Members: A Qualitative Analysis

Abstract: Hispanics in the U.S. experience significant health disparities. Using focus groups conducted in Spanish, we explored the perspectives of 172 Hispanic adults regarding their healthcare experiences. Many participants were female (64.5%) and primarily from Mexico (80%). Four major qualitative themes emerged: 1) provide us with information, 2) want attentive and respectful relationships, 3) want better care, and 4) perceived discrimination. Suboptimal patient-provider interactions were described. Research is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…3,4 Recent research with Hispanics living in regions not located along the Mexico-US border area indicated that Hispanics encounter barriers associated with a lack of health services that are culturally and linguistically tailored for Spanish-speaking patients or barriers to being able to receive timely care. [5][6][7] Receiving care in one's native language and that takes into consideration health literacy levels and cultural perspectives of nutrition, physical activity, treatments, and health beliefs has the potential to educate and empower patients in diabetes self-management behaviors and to become active partners in shared decision-making. 4,8 Given the diabetesrelated health disparities experienced by Hispanics and the barriers for Spanish-speaking patients, further investigation is warranted of circumstances that exacerbate diabetesrelated complications among this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Recent research with Hispanics living in regions not located along the Mexico-US border area indicated that Hispanics encounter barriers associated with a lack of health services that are culturally and linguistically tailored for Spanish-speaking patients or barriers to being able to receive timely care. [5][6][7] Receiving care in one's native language and that takes into consideration health literacy levels and cultural perspectives of nutrition, physical activity, treatments, and health beliefs has the potential to educate and empower patients in diabetes self-management behaviors and to become active partners in shared decision-making. 4,8 Given the diabetesrelated health disparities experienced by Hispanics and the barriers for Spanish-speaking patients, further investigation is warranted of circumstances that exacerbate diabetesrelated complications among this population.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies reported association between diabetes knowledge and glycemic control, 15,17,22 the SKILLD was not significantly correlated with A1C in the current study. This may be explained by considering that other factors, such as socioeconomic factors and getting access to care, [5][6][7] might also contribute to glycemic control among Hispanics with T2DM. The SKILLD showed good convergent validity with duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy was also seen as important to general health promotion among Latino dyads with chronic illness (McEwen et al, 2017). Latino females continue to be at risk for health disparities due to fatigue (Chang et al, 2018) and lack of respectful relationships with the health care team (Amirehsani et al, 2017). So if nurses desire to increase PA in Latino females, interventions which build on self-efficacy in both individuals and families are an important way to start.…”
Section: Discussionmentioning
confidence: 99%
“…We developed the interview guide (Appendix) based on review of the literature related to racial discordance, trust, and discrimination in clinical encounters [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Questions focused on racial and ethnic bias, our construct of interest.…”
Section: Interview Guide Developmentmentioning
confidence: 99%
“…Evidence demonstrates this bias negatively impacts patient's perceptions of the clinical encounter [7][8][9] treatment recommendations [10], and trust [11][12][13][14]. Although studies from various countries have explored patients' perceptions of race and/or ethnicity and bias in medicine [6,12,[14][15][16][17][18][19][20][21][22][23][24][25], patient perspectives on and suggestions for restoring the clinical and/or therapeutic relationship once bias is perceived are not known. Understanding these perspectives could inform the development of innovations in medical student education addressing implicit bias in clinical encounters.…”
Section: Introductionmentioning
confidence: 99%